Performance Evaluation of Local Body of Pokhara Metropolitan City - Dahal, Girdhari (Janapriya Journal of Interdisciplinary Studies, 2020)
Local governments are the closest unit of government to the people at grass root levels. The principal objective of this paper is to evaluate the performance of the local government of Pokhara Metropolitan City that lies in Kaski district, Nepal. This paper describes and analyzes the performance of the newly formed local government. It is based on the source of primary data from fieldwork with ground theory and secondary data- journal articles, books, Constitution of Nepal, 2015, act, rule, and regulations. The election of local government was held in Nepal in 2017, after 20 years. It is expected to bring political stability as well as peace and prosperity in Nepal. Nepal has been restructured as a federal democratic republic nation with federal, provinces and local government units- for sharing of power among the three tiers of government. Following the local elections, Pokhara Metropolitan City has already ratified more than six dozen laws (rules and regulations) for effective day to day service delivery to the local people. With grievances and grudges, the Nepalese people are experiencing the governance system of local bodies but the notion of people’s participation is more rhetoric. Also, financial capacity-both expenditure capacity and revenue generating capacity has severely limited the operational efficiency of local government. Moreover, transparency in public affairs has not been fully achieved yet.